Comparison of SPT and Vs-based Liquefaction Assessment on Young Volcanic Sediment: A Case Study in Bantul District of Yogyakarta, Indonesia - Amalina, Anisa Nur; Teuku Faisal Fathani; Wahyu Wilopo (Civil and Environmental Science Journal (CIVENSE), 2022)
On May 26, 2006, an earthquake of moment magnitude (Mw) 6.3 occurred in Yogyakarta. The damages found in Bantul were predicted to be caused by liquefaction. Moreover, liquefaction symptoms were found, such as a sand boil and lateral spreading. It inferred that the damage was controlled by the amplification factors from young volcanic sediments that are redeposited and altered volcaniclastics from the active Mount Merapi. This study compared subsurface conditions based on two field investigation methods (SPT and Shear Wave Velocity) and determined the liquefaction potential by considering groundwater and the region's seismicity. Several equations to represent the N-SPT and Vs data were also analyzed to obtain the most fitted equation. As a result, several equations used in this study were inadequate to properly correlate N-SPT and Vs. A comparison of safety factor values indicated that the liquefaction potential in the studied area on the Vs-based method is lower than the result from the SPT-based method.